Pelatihan dan Pembekalan Uji Sertifikasi Vokasi Tenaga Pengajar (Guru) Tingkat SMK Provinsi Maluku di Ambon - Fuad, Fuad Hasan Ohorella (LPPM UMRI, 2023)
Building is one of human needs and is used as a place to live and various other activities. Competence is a combination of knowledge, skills, values ​​and attitudes that are reflected in the habits of thinking and acting. SMK is a school that promises employment for its graduates, because in SMK students are prepared to have expertise or skills. For this reason, it is necessary to increase teachers (teachers) through a certification test. The method used in this service is training and debriefing with the stages of pre-test, presentation of material, post-test, and interviews. This activity was attended by 11 participants, the results of the pre-test stage were 63% of participants with a value range ≥ 60. After the debriefing process was then carried out again in the Post-Test stage, there was an increase in the percentage of participant scores by 27% compared to the pre-test with a range of values ​​≥ 60 as much 90%, then continued with the participant interview session Showing results with a range of values ​​≥ 60 as much as 100% means that after the interview process is complete 11 participants are declared successful